Redox controls on sediment–hosted Cu mineralization and possible microbial influence in the Redbeds Series, Guska area, Zagros Foreland Basin, Kurdistan Region, Iraq - Mohammad Pirouei; Azad Tahir Saeed; Yousif Osman Mohammad; Shahrokh Rajabpour; Bzhar A. Delizy; Shaheen Ali Shaheen; Arkan Osman Sharazwri (Applied Geochemistry, 2026)

Ecological Vulnerability of Bangladesh’s Major Wetlands: A Comparative Review with Special Reference to Ratargul Swamp Forest - Tahia Siddika; Md. Mominul Islam; Md. Abul Kalam Azad; Md. Najmul Kabir; Arifur Rahman; Mrityunjoy Kunda; A. k. M. Rashidul Alam; Md. Anowarul Islam (Wetlands, 2026)

Exposure-safety analyses of talazoparib in combination with enzalutamide in patients with metastatic castration-resistant prostate cancer (mCRPC) in the TALAPRO-2 trial - Yibo Wang; Mark Hadigol; Victor Ruberio Lincha; Justin Hoffman; Arun A. Azad; Neeraj Agarwal; Nobuaki Matsubara; Fabian Zohren; Liza DeAnnuntis; Diane D. Wang (Journal of Pharmacokinetics and Pharmacodynamics, 2026)

DNA barcoding resolves the identity and invasion pathway of the non-indigenous goby genus Rhinogobius (Gobiiformes: Oxudercidae) in the Caspian Sea basin, and reveals cryptic diversity within the native range - Azad Teimori; Hamid Reza Esmaeili; Keyvan Abbasi; Fereshteh Pourhosseini; Mina Motamedi; Namiq Mustafayev; Boris A. Levin (Regional Studies in Marine Science, 2026)

Minimum tension reinforcement ratio for beams made of pumice aggregate lightweight concrete - Azad A. Mohammed; Azhar J. Nimat (Innovative Infrastructure Solutions, 2026)

Variation in patterns of production and water-use efficiency among agroecosystems - Olivia L. Hajek; Nicole E. Kaplan; Shefali Azad; Philip A. Fay; Makki Khorchani; Amanda M. Nelson; Adam P. Schreiner-McGraw; Lori J. Abendroth; Claire Baffaut; John Baker; Brandon T. Bestelmeyer; Elizabeth H. Boughton; et al. (Science of The Total Environment, 2025)

The role of waste glass powder in alkali-silica reaction mitigation: Transforming glasscrete durability through chemical composition dynamics - Maryam Basil Ishaq; Ahmed Salih Mohammed; Azad A. Mohammed (Sustainable Chemistry and Pharmacy, 2025)

Performance of single and group anchors embedded in polypropylene fiber high strength concrete and relation with non-destructive response - Azad A. Mohammad; Lawand D. Ahmed (Innovative Infrastructure Solutions, 2025)

Chemical characterization and performance optimization of waste glass-modified concrete for sustainable construction - Maryam Basil Ishaq; Ahmed Salih Mohammed; Azad A. Mohammed (Sustainable Chemistry and Pharmacy, 2025)

Nanomineralzyme as a novel sustainable class of nanozyme: Chalcopyrite-based nanozyme for the visual detection of total antioxidant capacity in citrus fruit - Sameera Sh. Mohammed Ameen; Azad H. Alshatteri; Dnya A. Latif; Yousif O. Mohammad; Khalid M. Omer (Food Chemistry, 2025)

Novel exploration of chemical compounds in mono-variate, Bi-variate, and multi-variate scenarios of waste glass powder as a cement replacement in concrete - Maryam Basil Ishaq; Ahmed Salih Mohammed; Azad A. Mohammed (Sustainable Chemistry and Pharmacy, 2025)

Whole-Genome Analysis of Multidrug-Resistant Klebsiella pneumoniae Kp04 Reveals Distinctive Antimicrobial and Arsenic-Resistance Genomic Features: A Case Study from Bangladesh - Md. Javed Foysal; Farhana Momtaz; A. M. Masudul Azad Chowdhury; Afroza Akter Tanni; Asma Salauddin; Md. Zahid Hasan; Sohana Akter Mina; Nahid Sultana; Sanjoy Kanti Biswas; Kamrul Islam; Alfred Tay; Adnan Mannan (Current Microbiology, 2025)

A biostratigraphic study of the Govanda Formation from two representative localities of Iraqi Kurdistan Region - Arkan O. Sharazwri; Azad T. Saeed; Dana N. Ridha; Soran O. A. Kharajiany (Carbonates and Evaporites, 2024)

Oncoinformatic screening of the gene clusters involved in the HER2-positive breast cancer formation along with the in silico pharmacodynamic profiling of selective long-chain omega-3 fatty acids as the metastatic antagonists - A K M Helal Morshed; Salauddin Al Azad; Md. Abdur Rashid Mia; Mohammad Fahim Uddin; Tanzila Ismail Ema; Rukaiya Binte Yeasin; Sanjida Ahmed Srishti; Pallab Sarker; Rubaita Younus Aurthi; Farhan Jamil; Nure Sharaf Nower Samia; Partha Biswas; et al. (Molecular Diversity, 2023)

Stand level carbon stocks in the soil-vegetation system of the coastal mangrove plantations in Bangladesh: Effect of stand age and choice of species - Md. Nabiul Islam Khan; Atikur Rahman; Gazi A. Rahman Nahid; Md. Abir Hasan; Md. Rafikul Islam; Md. Salim Azad; Abdus Subhan Mollick (Regional Studies in Marine Science, 2023)

Tunnel Support Validation Using Numerical Modelling: A Case Study from NW, Himalaya, India - Md Alquamar Azad; A. K. Naithani; Saurav Shekhar; Seraj Ahmad; S. K. Singh (Geotechnical and Geological Engineering, 2023)

Numerical study of the effects of coastal currents and meso-scale eddies on the spread of pollution in the Persian Gulf - H. Mehrfar; A. Raeisi; M. Torabi Azad; S. M. R. Reisosadat (International Journal of Environmental Science and Technology, 2023)

Green synthesis of nano-silica from olivine rock and its impact on the mechanical performance of geopolymer concrete composites - Hemn Unis Ahmed; Rabar H. Faraj; Aso Q. Hassan; Yousif Osman Mohammad; Khalid M. Omer; Ahmed S. Mohammed; Azad A. Mohammed (Innovative Infrastructure Solutions, 2023)

Target-specificity of different amyrin subunits in impeding HCV influx mechanism inside the human cells considering the quantum tunnel profiles and molecular strings of the CD81 receptor: a combined in silico and in vivo study - Anika Jabin; Mohammad Fahim Uddin; Salauddin Al Azad; Ashfaque Rahman; Fawzia Tabassum; Pritthy Sarker; A K M Helal Morshed; Samiur Rahman; Fatima Fairuz Raisa; Musfiqur Rahman Sakib; Abeer Hasan Olive; Tabassum Islam; et al. (In Silico Pharmacology, 2023)

Compressive strength of geopolymer concrete composites: a systematic comprehensive review, analysis and modeling - Hemn Unis Ahmed; Ahmed S. Mohammed; Shaker M. A. Qaidi; Rabar H. Faraj; Nadhim Hamah Sor; Azad A. Mohammed (European Journal of Environmental and Civil Engineering, 2023)

Preparation of Free-Flowing Spray-Dried Amorphous Composites Using Neusilin® - Zhixing Lin; Kai Zheng; Mohammad A. Azad; Rajesh N. Davé (AAPS PharmSciTech, 2023)

Improved Aerosolization Stability of Inhalable Tobramycin Powder Formulation by Co-Spray Drying with Colistin - Vaibhav Pathak; Heejun Park; Dmitry Zemlyanov; Sonal V. Bhujbal; Maizbha Uddin Ahmed; Mohammad A. K. Azad; Jian Li; Qi Tony Zhou (Pharmaceutical Research, 2022)

Modeling the compressive strength of eco-friendly self-compacting concrete incorporating ground granulated blast furnace slag using soft computing techniques - Rabar H. Faraj; Azad A. Mohammed; Khalid M. Omer (Environmental Science and Pollution Research, 2022)

Proposing several model techniques including ANN and M5P-tree to predict the compressive strength of geopolymer concretes incorporated with nano-silica - Hemn Unis Ahmed; Ahmed S. Mohammed; Azad A. Mohammed (Environmental Science and Pollution Research, 2022)

Multicomponent Droplet Drying Modeling Based on Conservation and Population Balance Equations - Sadegh Poozesh; Faisal Algasem; Mohammad A. Azad; Patrick J. Marsac (Pharmaceutical Research, 2022)

Soft computing techniques to predict the compressive strength of green self-compacting concrete incorporating recycled plastic aggregates and industrial waste ashes - Rabar H. Faraj; Azad A. Mohammed; Khalid M. Omer; Hemn Unis Ahmed (Clean Technologies and Environmental Policy, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Spatial distribution modeling of the wild boar (Sus scrofa) under current and future climate conditions in Iraq - Nabaz R. Khwarahm; Korsh Ararat; Barham A. HamadAmin; Peshawa M. Najmaddin; Azad Rasul; Sarchil Qader (Biologia, 2022)

Impact of Critical Material Attributes (CMAs)-Particle Shape on Miniature Pharmaceutical Unit Operations - Mohammad A. Azad; Gerard Capellades; Allison B. Wang; David M. Klee; Gregory Hammersmith; Kersten Rapp; David Brancazio; Allan S. Myerson (AAPS PharmSciTech, 2021)
The U.S. Food and Drug Administration (FDA) emphasizes drug product development by Quality by Design (QbD). Critical material attributes (CMAs) are a QbD element that has an impact on pharmaceutical operations and product quality. Pharmaceutical drugs often crystallize as needle-shaped (a CMA) particles and affect the process due to poor flowability, low bulk density, and high compressibility, and eventually the product performance. In this study, the product obtained from crystallization was needle-shaped Ciprofloxacin HCl (CIPRO), formed lumps during drying, and compacted during processing through feeders. To delump small amounts of materials and break the needles, multiple available devices (mortar-pestle, Krups grinder) and custom-made grinder were assessed before formulation. The processed CIPRO powder was then used to make tablets in the miniature tablet manufacturing unit developed by the team at MIT. The critical quality attributes (CQA) of the tablets, set by the United States Pharmacopeia (USP), were then assessed for the drug powder processed with each of these devices. Powder properties comparable to commercial CIPRO were obtained when the custom MIT-designed grinder was used, leading to tablets that meet the USP criteria, with comparable dissolution profiles of those for marketed CIPRO tablets. This study demonstrates how needle-shaped crystals have an impact on pharmaceutical operations, even if it is on a miniature scale, and how proper shape and subsequent flow properties can be obtained by processing the particles through the MIT team-designed grinder. Graphical Abstract

Investigation and evaluation of salinity gradient power in Arvand River estuary using pressure retarded osmosis (PRO) method - S. Khodadadian Elikaiy; K. Lari; M. Torabi Azad; A. Sabetahd Jahromi; A. Mohseni Arasteh (International Journal of Environmental Science and Technology, 2021)

Screening of bread wheat (Triticum aestivum L.) genotypes under drought stress conditions using multivariate analysis - M. Arifuzzaman; S. Barman; S. Hayder; M. A. K. Azad; M. T. S. Turin; M. A. Amzad; M. S. Masuda (Cereal Research Communications, 2020)

Spatiotemporal mapping mangroves of Tengragiri wildlife sanctuary under Barguna district of Bangladesh using freely available satellite imagery - Md. Mozahidul Islam; Ruhul Mohaiman Chowdhury; A. K. M. Mostafa Zaman; Md. Saifur Rahman; Md. Nazrul Islam; Ajit Kumar Rudra; Md. Salim Azad (Modeling Earth Systems and Environment, 2020)

On-Demand Manufacturing of Direct Compressible Tablets: Can Formulation Be Simplified? - Mohammad A. Azad; Juan G. Osorio; Allison Wang; David M. Klee; Mary E. Eccles; Erin Grela; Rebecca Sloan; Gregory Hammersmith; Kersten Rapp; David Brancazio; Allan S. Myerson (Pharmaceutical Research, 2019)

Climate change increases potential plant species richness on Puerto Rican uplands - Azad Henareh Khalyani; William A. Gould; Michael J. Falkowski; Robert Muscarella; María Uriarte; Foad Yousef (Climatic Change, 2019)

Impact of Tidal Phase on Inundation and Thrust Force Due to Storm Surge - A. S. M. Alauddin Al Azad; Kazi Samsunnahar Mita; Md. Wasif Zaman; Marin Akter; Tansir Zaman Asik; Anisul Haque; Mohammad Asad Hussain; Md. Munsur Rahman (Journal of Marine Science and Engineering, 2018)
Impact of storm surge largely varies depending on the tidal phase during the landfall of a tropical cyclone. This study investigates comparative variance in inundation condition and thrust force for an identical cyclone during low tide and high tide by applying a numerical model (Delft3D) and a semi-analytical model (DFM). A moderate strength cyclone, Mora, which made landfall on Bangladesh coast in May 2017 is selected to study its impact on land during low tide and high tide. Actual landfall time of Mora was during low tide. To study the impact of storm surge during high tide, a synthetic cyclone is created which has similar strength and track to that of Mora but makes landfall during high tide. The results show that inundation depth, inundation extent, and thrust force increase when a cyclone makes landfall during high tide compared to the condition when the cyclone makes landfall during low tide. But the relation between storm surge impact and tidal phase is not linear. It depends on the land topography of the location, direction of cyclone movement, direction and magnitude of water velocity and wind velocity, gradients of water surface and wind velocity, and proximity and position of the location with respect to cyclone track.

Correction to: Polymyxin B causes DNA damage in HK-2 cells and mice - B. Yun; T. Zhang; M. A. K. Azad; J. Wang; C. J. Nowell; P. Kalitsis; T. Velkov; D. F. Hudson; J. Li (Archives of Toxicology, 2018)

Polymyxin B causes DNA damage in HK-2 cells and mice - B. Yun; T. Zhang; M. A. K. Azad; J. Wang; C. J. Nowell; P. Kalitsis; T. Velkov; D. F. Hudson; J. Li (Archives of Toxicology, 2018)

Fire weather and likelihood: characterizing climate space for fire occurrence and extent in Puerto Rico - Ashley E. Van Beusekom; William A. Gould; A. Carolina Monmany; Azad Henareh Khalyani; Maya Quiñones; Stephen J. Fain; Maria José Andrade-Núñez; Grizelle González (Climatic Change, 2018)

Virulence of Entomopathogenic Fungus, Metarhizium anisopliae to Sweetpotato Whitefly, Bemisia tabaci (Hemiptera: Aleyrodidae) Under Osmotic Stress - Md. Touhidul Islam; Dzolkhifli Omar; A. K. M. Azad Shah; Md. Fakrul Hasan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

A Study of the Performances of Different Turbulence Schemes in Numerical Simulation of Hydrodynamics of a Semi-Closed Sea (Persian Gulf) - M. Mohandesi Namin; A. A. Bidokhti; A. Karami Khaniki; I. Hasan Zadeh; M. Torabi Azad (Marine Geodesy, 2016)

Efficient Water Use for Sustainable Irrigation Industry - Md A. S. Azad; Tihomir Ancev; Francesc Hernández-Sancho (Water Resources Management, 2015)

Prevalence of various chromosomal disorders diagnosed in a selected population suspected of having genetic diseases from different regions of the valley of Kashmir, North India - Arshad A. Pandith; Tahir M. Malla; Fayaz A. Dar; Shahnawaz A. Sheikh; Qayser Yousuf; Shehjar Faheem; Farhat Shawl; Niyaz A. Azad; Shahid Baba; Mushtaq A. Siddiqi; Zafar A. Shah (The Nucleus, 2013)

Genome of alkaliphilic Bacillus pseudofirmus OF4 reveals adaptations that support the ability to grow in an external pH range from 7.5 to 11.4 - Benjamin Janto; Azad Ahmed; Masahiro Ito; Jun Liu; David B. Hicks; Sarah Pagni; Oliver J. Fackelmayer; Terry‐Ann Smith; Joshua Earl; Liam D.H. Elbourne; Karl Hassan; Ian T. Paulsen; et al. (Environmental Microbiology, 2011)
Summary Bacillus pseudofirmus OF4 is an extreme but facultative alkaliphile that grows non‐fermentatively in a pH range from 7.5 to above 11.4 and can withstand large sudden increases in external pH. It is a model organism for studies of bioenergetics at high pH, at which energy demands are higher than at neutral pH because both cytoplasmic pH homeostasis and ATP synthesis require more energy. The alkaliphile also tolerates a cytoplasmic pH > 9.0 at external pH values at which the pH homeostasis capacity is exceeded, and manages other stresses that are exacerbated at alkaline pH, e.g. sodium, oxidative and cell wall stresses. The genome of B. pseudofirmus OF4 includes two plasmids that are lost from some mutants without viability loss. The plasmids may provide a reservoir of mobile elements that promote adaptive chromosomal rearrangements under particular environmental conditions. The genome also reveals a more acidic pI profile for proteins exposed on the outer surface than found in neutralophiles. A large array of transporters and regulatory genes are predicted to protect the alkaliphile from its overlapping stresses. In addition, unanticipated metabolic versatility was observed, which could ensure requisite energy for alkaliphily under diverse conditions.

Coastal Aquaculture Development in Bangladesh: Unsustainable and Sustainable Experiences - A. Kalam Azad; Kathe R. Jensen; C. Kwei Lin (Environmental Management, 2009)

Plant regeneration through somatic embryogenesis of a medicinal plant, Phellodendron amurense Rupr. - M. A. K. Azad; S. Yokota; F. Begum; N. Yoshizawa (In Vitro Cellular & Developmental Biology - Plant, 2009)

Zinc, Manganese, Calcium, Copper, and Cadmium Level in Scalp Hair Samples of Schizophrenic Patients - Md. Ashrafur Rahman; Mohammad Abul Kalam Azad; Md. Iqbal Hossain; M. M. A. Shalahuddin Qusar; Wasimul Bari; Farida Begum; S. M. Imamul Huq; Abul Hasnat (Biological Trace Element Research, 2009)

Antibacterial activity of two limonoids from Swietenia mahagoni against multiple-drug-resistant (MDR) bacterial strains - A. K. M. Shahidur Rahman; A. K. Azad Chowdhury; Husne-Ara Ali; Sheikh Z. Raihan; Mohammad S. Ali; Lutfun Nahar; Satyajit D. Sarker (Journal of Natural Medicines, 2009)

Microbial intervention for better fish health in aquaculture: the Indian scenario - A. Panigrahi; I. S. Azad (Fish Physiology and Biochemistry, 2007)

Assessing morphological and isozyme variation of jackfruit (Artocarpus heterophyllus Lam.) in Bangladesh - A. K. Azad; J. G. Jones; N. Haq (Agroforestry Systems, 2007)

Plant regeneration from mesophyll protoplasts of a medicinal plant, Phellodendron amurense rupr. - M. A. K. Azad; S. Yokota; F. Ishiguri; N. Yoshizawa (In Vitro Cellular & Developmental Biology - Plant, 2006)

In vitro regeneration of the medicinal woody plant Phellodendron amurense Rupr. through excised leaves - M. A. K. Azad; S. Yokota; T. Ohkubo; Y. Andoh; S. Yahara; N. Yoshizawa (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Pseudomonas aeruginosa dihydroorotases: a tale of three pyrCs - Dayna M. Brichta; Kamran N. Azad; Pooja Ralli; Gerard A. O’Donovan (Archives of Microbiology, 2004)

Fine mapping a gene for pediatric gastroesophageal reflux on human chromosome 13q14 - Fen Ze Hu; Joseph Donfack; Azad Ahmed; Richard Dopico; Sandra Johnson; J. Christopher Post; Garth D. Ehrlich; Robert A. Preston (Human Genetics, 2004)

Kinetics of ingested host immunoglobulin G in hemolymph and whole body homogenates during nymphal development of Dermacentor variabilis and Ixodes scapularis ticks (Acari: Ixodidae). - Jefferson A. Vaughan; Daniel E. Sonenshine; Abdu F. Azad (Experimental and Applied Acarology, 2002)

A C-terminal domain of HIV-1 accessory protein Vpr is involved in penetration, mitochondrial dysfunction and apoptosis of human CD4+ lymphocytes - C. Arunagiri; I. Macreadie; D. Hewish; A. Azad (Apoptosis, 1997)

Expression and analysis of the NS2 protein of influenza A virus - A. C. Ward; L. A. Castelli; A. C. Lucantoni; J. F. White; A. A. Azad; I. G. Macreadie (Archives of Virology, 1995)

Expression and characterisation of the influenza A virus non-structural protein NS1 in yeast - A. C. Ward; A. A. Azad; I. G. Macreadie (Archives of Virology, 1994)